CHARACTERISTICS OF SOME ASPECTS OF THE INTERNATIONAL STUDENTS’ ADAPTATION IN MEDICAL UNIVERSITY - Яворський, А. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In order to study some aspects of adaptation to life and education in Ukraine, 159 international students of Ivano-Frankivsk National Medical University were interviewed. It has been established that a significant part of international students after 5 years of stay in Ukraine still do not find a good understanding in the academic group (21.4%), and complain about conflicts with teachers (22.0%) and the inhabitants of the city (29.6%), not only because of the language barrier (38.4%), but also because of their bias towards foreigners (31.3%). It is shown that the adaptation of foreigners to the new conditions for their study and residence depends on the student’s native region of residence, and therefore on cultural, religious, ethnic and other characteristics. Conclusion. To improve the adaptation of international students the university complex of educational, scientific, educative and other measures involving psychological help if needed should to develop.